Investigating the role of urban furniture in improving the quality of urban environment (Case study: Bandar Abbas city) - Sepideh Raeisi Qanavati; Marzieh Moghli; Mohammad Ebrahim Afifi (تحقیقات کاربردی علوم جغرافیایی)
With the increasing expansion of urbanization and the increase in the population of urban dwellers and the resulting problems, it is becoming increasingly necessary to provide facilities for the well-being of citizens. Today, the importance and role of urban furniture in urban service and beautification is not hidden from anyone, and urban furniture is one of the essential and inseparable components of cities. The purpose of this study is to investigate the role of urban furniture in improving the quality of urban environment, Bandar Abbas city, which has been done by descriptive-analytical method. Data collection has been done using two methods of library and field (questionnaire). The statistical population of this study consists of citizens of Bandar Abbas, 384 of whom were selected using Cochran's formula and research questionnaire by simple random method. Distributed among them. The research questionnaire was created by a researcher whose validity was confirmed by experts in a formal and superficial manner. And its reliability was confirmed using Cronbach's alpha coefficient. In order to achieve the objectives of the research, single-sample T-test and simple linear regression were used in SPSS25 software environment. The research findings showed that the urban furniture of Bandar Abbas is not in a good condition in terms of fitness and beauty, optimal distribution and citizens' satisfaction with the furniture of Bandar Abbas. The study of research hypotheses showed that urban furniture has a positive and significant effect on the quality of urban environment and its components, ie beautifying the environment, creating a suitable environment for social activities and increasing the vitality of the urban environment.